CHARACTERIZATION OF ZINC OXIDE AS DIELECTRIC CERAMICS FOR REDUCTION OF INTERFACIAL TENSION BETWEEN OIL AND WATER - YAHAYA, AHMAD WAFIY ADLI (IRC, 2017)
Generally, the application of nanotechnology is widely used in daily life. Nanotechnology helps to improve the characteristic and properties of the material. Most of the application of the nanoparticles is to enhance the ability of the material which improve their performance during its operation. Nanoparticles also would help to increase the wettability of the particles. The increasing wettability of the material or substances will lead to the decreasing of the interfacial tension between the surfaces. In the oil and gas industry, oil that is extracted is not optimum due to high interfacial tension between oil and water. Thus, this research was conducted to study the effect of different concentration of zinc oxide nanoparticles to the reduction of interfacial tension between oil and water. This project is mainly to investigate the changes on the physical and molecular level properties of the oil and water after the zinc oxide nanoparticle is used as additional component in the brine solution to increase mobility of the oil. The characterization of zinc oxide is done by using XRD and FESEM. For this experiment, the IFT is not directly measured by using IFT machine instead, the IFT is analyzed through the contact angle testing and pendant drop testing. The contact angle and pendant drop test were conducted by using the goniometer machine, to justify the changes of interfacial tension between oil and water. Increasing the concentration of the nanofluid, the contact angle and surface tension are decreasing. It is confirmed that the interfacial tension between oil and water is decreasing along with the increasing concentration of zinc oxide nanofluid. The graph of concentration of nanofluid against the contact angle and surface tension will be plotted by the data obtained from the contact angle testing and pendant drop testing which to analyze the interfacial tension of the water to the zinc oxide. In the nutshell, this study can prove that zinc oxide nanoparticles have the wettability properties that possess a high potential to replace the current method of reducing the interfacial tension between oil and water and used in the oil and gas industry as one of the Enhanced Oil Recovery (EOR) alternatives.